The biomechanical effect of warm-up stretching strategies on landing mechanics in female volleyball athletes - Avedesian, J. M.; Judge, L. W.; Wang, H.; Dickin, D. C. (Sports Biomechanics, 2020)
Female volleyball athletes incorporate dynamic and static stretching into a warm-up, with evidence generally supporting dynamic stretching to improve performance. However, the effects of these stretching practices on injury risk during subsequent volleyball manoeuvres have yet to be fully elucidated in the warm-up literature. Three-dimensional kinematic data associated with non-contact, lower extremity injury were recorded on 12 female collegiate club volleyball athletes during unilateral landing tasks on the dominant and non-dominant limb. Participants performed landings as part of a volleyball-simulated manoeuvre prior to and post-dynamic (DWU) and combined dynamic-static (CDS) warm-ups. A significant reduction in non-dominant hip adduction angle was found at 15 min post CDS warm-up (p = 0.016; d = 0.38), however, no other warm-up differences were detected. The non-dominant limb demonstrated greater knee abduction (p = 0.006; d = 0.69) and internal rotation angle (p = 0.004; d = 0.88), suggesting that this limb demonstrates more risky landing patterns that are potentially due to altered trunk positioning upon landing. The results show that the majority of selected landing kinematics are unaffected by additional static stretching to a dynamic warm-up and that the non-dominant limb may be at a higher injury risk in female volleyball athletes.